Permissible Intraabdominal Hypertension following Complex Abdominal Wall Reconstruction. Issue 4 (October 2015) - Petro, Clayton C.; Raigani, Siavash; Fayezizadeh, Mojtaba; Rowbottom, James R.; Klick, John C.; Prabhu, Ajita S.; Novitsky, Yuri W.; Rosen, Michael J.
Abstract : Background: Repair of hernias with loss of domain can lead to elevated intraabdominal pressure. The authors aimed to characterize the effects of elective hernia repair on intraabdominal pressure, as well as its predictors and association with negative outcomes. Methods: Patients undergoing elective hernia repair requiring myofascial release had intraabdominal and pulmonary plateau pressures measured preoperatively, postoperatively, and on the morning of the first postoperative day. Loss of domain was measured by preoperative computed tomography. Outcome measures included predictors of an increase in plateau pressure, respiratory complications, and acute kidney injury. Results: Following 50 consecutive cases, diagnoses of intraabdominal hypertension (92 percent), abdominal compartment syndrome (16 percent), and abdominal perfusion pressure less than 60 mmHg (24 percent) were determined. Changes in intraabdominal pressure (preoperative, 12.7 ± 4.0 mmHg; postoperative, 18.2 ± 5.4 mmHg; postoperative day 1, 12.9 ± 5.2 mmHg) and abdominal perfusion pressure (preoperative, 74.7 ± 15.7; postoperative, 70.0 ± 14.4; postoperative day 1, 74.9 ± 11.6 mmHg) consistently resolved by postoperative day 1, and were not associated with respiratory complications or acute kidney injury. Patients who remained intubated postoperatively for an elevation in pulmonary plateau pressure (≥6 mmHg) all demonstrated an improvement in plateau pressure by postoperative day 1 (preoperative, 18.9 ± 4.5 mmHg; postoperative, 27.4 ± 4.0 mmHg; postoperative day 1, 20.1 ± 3.7 mmHg), and could be identified preoperatively as having a hernia volume of greater than 20 percent of the abdominal cavity ( p < 0.001), but were still more likely to have postoperative respiratory events ( p = 0.01). Conclusions: Elevated intraabdominal pressure following elective hernia repair requiring myofascial releases is common but transient. Change in plateau pressure by 6 mmHg or more following repair can be expected with a loss of domain greater than 20 percent and is a more useful surrogate than intraabdominal pressure measurements with regard to predicting postoperative pulmonary complications. The perception and management of elevated intraabdominal pressure should be considered distinct and "permissible" in this context.